1930
DOI: 10.1098/rspa.1930.0189
|View full text |Cite
|
Sign up to set email alerts
|

The swelling of charcoal. Part I.—Preliminary experiments with water vapour, carbon dioxide, ammonia, and sulphur dioxide

Abstract: The experiments of Meehan having shown that charcoal increases in volume when taking up carbon dioxide, it became an obvious step to correlate this expansion with the quantity of gas adsorbed. In this paper a form of extensometer is described which, while sufficiently sensitive and accurate for the measurement of the percentage linear expansion ( x ) of a rod of wood charcoal, was yet compact enough to permit its being sealed up in an all-glass apparatus, so that simultaneous determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…[3,10,11] This relation is the result of two equilibrium conditions, one thermodynamic and the other mechanic. [9] This means that a stress external to the porous layer can change the adsorbed amount and hence the condensation pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,10,11] This relation is the result of two equilibrium conditions, one thermodynamic and the other mechanic. [9] This means that a stress external to the porous layer can change the adsorbed amount and hence the condensation pressure.…”
Section: Resultsmentioning
confidence: 99%
“…We have no information on the elastic deformation (δa/a) of the supported porous layer and the corresponding membrane during N 2 adsorption experiment, but several investigators [3,10,11] have shown that, in the region preceding capillary condensation, the linear deformation of porous materials is related to the adsorbed amount by the equation…”
Section: Elastic Deformation Of the Porous Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Meeham 1927; Bangham and Fakhoury 1930;Hains and McIntosh 1947;Amberg and McIntosh 1952;Hiller 1964;Bentz et al 1998 ). However, significant differences in sorption isotherm and length-change isotherm between hardened cement paste (hereafter referred to as hcp) and other porous materials are known to exist, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a series of experiments, [71][72][73][74] which all showed monotonic expansion of charcoal samples with increased adsorbate pressure, Bangham concluded that the measured linear strain is proportional to the decrease in the surface energy c of a solid, caused by adsorption…”
Section: Monotonic Expansion: Bangham's Lawmentioning
confidence: 99%